2015
DOI: 10.7554/elife.06184
|View full text |Cite
|
Sign up to set email alerts
|

Siglec receptors impact mammalian lifespan by modulating oxidative stress

Abstract: Aging is a multifactorial process that includes the lifelong accumulation of molecular damage, leading to age-related frailty, disability and disease, and eventually death. In this study, we report evidence of a significant correlation between the number of genes encoding the immunomodulatory CD33-related sialic acid-binding immunoglobulin-like receptors (CD33rSiglecs) and maximum lifespan in mammals. In keeping with this, we show that mice lacking Siglec-E, the main member of the CD33rSiglec family, exhibit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 73 publications
2
55
0
Order By: Relevance
“…The results of other studies involving NADPH oxidase-deficient mice confirmed a phagocyte-derived ROS-mediated anti-inflammatory function, which contributes to the suppression of neutrophil recruitment in the lung [64,65]. Schwarz et al [66] speculated that Siglec-E evolved in mammals because it helped control ROS levels during chronic inflammation. However, McMillan et al [13] demonstrated that Siglec-E affects ROS homeostasis.…”
Section: Siglec-e As An Inhibitor Of Neutrophil Recruitmentsupporting
confidence: 50%
“…The results of other studies involving NADPH oxidase-deficient mice confirmed a phagocyte-derived ROS-mediated anti-inflammatory function, which contributes to the suppression of neutrophil recruitment in the lung [64,65]. Schwarz et al [66] speculated that Siglec-E evolved in mammals because it helped control ROS levels during chronic inflammation. However, McMillan et al [13] demonstrated that Siglec-E affects ROS homeostasis.…”
Section: Siglec-e As An Inhibitor Of Neutrophil Recruitmentsupporting
confidence: 50%
“…The proposed link between bat longevity, viral tolerance and antiinflammatory response is certainly plausible also in the light of available evidence from other species. Number of anti-inflammatory CD33rSiglec family genes shown strong positive correlation with maximum life span in 14 mammalian species (Schwarz et al, 2015) and longer life spans of laboratory rat strains have been linked with maintaining ability to synthesize not only proinflammatory TNF, but also anti-inflammatory Il-10 (Dimitrijević et al, 2014). Interestingly, increased production of Il-10 promotes viral persistence (Brooks et al, 2006) and higher levels of serum Il-10 are associated with asymptomatic infections in humans (Guiyedi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of sialic acids with sialidase Neu1 can disrupt this interaction, resulting in activation of inflammatory processes. LPS stimulation induces exaggerated recruitment of neutrophils in the lung in Siglec-E knock-out mice (14,15). In mouse models of bacterial infection (16), tumor growth (17), and sepsis (18), Siglec-E plays a critical role in the pathogenesis of diseases.…”
Section: Cd33-related Siglecs Are a Family Of Proteins Widely Expressmentioning
confidence: 99%
“…In mouse models of bacterial infection (16), tumor growth (17), and sepsis (18), Siglec-E plays a critical role in the pathogenesis of diseases. Siglec-E also modulates oxidative stress that leads to aging (15).…”
Section: Cd33-related Siglecs Are a Family Of Proteins Widely Expressmentioning
confidence: 99%
See 1 more Smart Citation